Game design : from blue sky to green light. - Todd, Deborah, ....- (Wellesley : A K Peters, 2007)
This book takes a real-world, in-depth journey through the game-design process, from the initial blue sky sessions to pitching for a green light. The author discusses the decision and brainstorming phase, character development and story wrap, creation of content and context outlines, flowcharting game play, and creating design documents. Special features include examples of both classic and contemporary games, and interviews with many of the game industry's brightest professionals who share their insights on key elements in game design, and their analysis on what makes a game a blockbuster hit. This book is a perfect guide for the novice, student, and game enthusiast interested in learning the nuts and bolts of the computer-game industry.
Keywords: Computerspelen